One-pot transition-metal-free cascade synthesis of thieno[2, 3-c]coumarins from chromones. Issue 106 (1st November 2016) - Yang, Yuhong; Qi, Xueyu; Liu, Ruiling; He, Qian; Yang, Chunhao
Abstract : A one-pot transition-metal-free, base-mediated synthesis of a novel series of functionalized thieno[2, 3- c ]coumarins has been developed through a cascade reaction from chromones. Abstract : A one-pot transition-metal-free, base-mediated synthesis of a novel series of functionalized thieno[2, 3- c ]coumarins via a cascade reaction from chromones has been developed. This cascade reaction involves a Michael addition–Knoevenagel condensation–intramolecular cyclization. This transformation proceeds under mild conditions and gives various thieno[2, 3- c ]coumarins in good-to-excellent yields. The methodology is tolerant of a wide range of functional groups and applicable to library synthesis.